Traditional wooden houses in Maringá (Brazil): ICT in planning research. Issue 2 (September 2019) - Nakamura-Gonino, Camila; Virtudes, Ana; Silva, Ricardo
Abstract: In many cities, the examples of traditional architecture are being replaced by contemporary buildings, without any strategies in order to preserve a specific period of the urban and housing histories. These legacies are witnesses of particular features in terms of local communities, societies, political environments, urban morphologies or architectural languages. In this sense, this article presents the case study of the traditional wooden houses in the city of Maringá in Paraná (Brazil). There is a set of buildings which still remain among the existing urban fabric. However, every year some of them are destroyed in order to give room for new ways of designing the city. The methodological approach is based on the ICT (information and communication technologies) as a tool to study the features of these traditional wooden buildings.